Jenis-Jenis Serangga Pengunjung Bunga NeriumoleanderLinn.(Apocynaceae) di Kecamatan Pauh, Padang - Weni Yuliani; - Dahelmi; - Syamsuardi (Universitas Andalas, 2013)
An inventory of insects visiting the flower of Nerium oleander Linn (Apocynaceae) had been conducted in Pauh subdistrict Padang City from Septemberto December 2012. The purpose of the study was to determine the visitor insect species of Nerium oleander flower. Observation, scan sampling and direct collection method by using insect net were used in this study. Insects were identified at Laboratory of Animal Taxonomy, Biology Department, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The results showed that 23 species of insects that belong to 19 genera, 11 families and 4 orders were recorded. The visitor insects were dominated by Lepidoptera order (56.52%) followed by Hymenoptera (30.43%), Coleoptera (8.7%)and Diptera (4.35%).Keywords: Nerium oleander, insects, visitors, flower, species